Pemanfaatan sludge ipal industri genteng mutiara untuk substitusi bahan baku pembuatan bata beton (paving block) - AJI, Awaluddin Setya ([Yogyakarta] : Universitas Gadjah Mada, 2010)
Total production of waste generated by the “Genteng Mutiara” (GM) roof tile industry is 4 to 6 m3/week. The sludge is then piled onto an empty land owned by GM. Generally, the sludge contains SiO2, Al2O3, Fe2O3 and SO3. Moreover, it has soft texture and contains oil. Based on those conditions, the researcher attempted to utilize the sludge as a substitute raw material for concrete roof tile. The research findings showed that the concrete roof tiles which were composed with different combination of sludge do not meet the ISO (SNI) criteria. For that reason, further research was carried out. The sludge was then used to substitute fly ash in paving blocks production. The material which was utilized in the research is the sludge which firstly wasted from the tile production machine t ype Garuda, Ramayana and Royal. Basically, paving blocks are produced using the raw material as follow: cement, fly ash, aggregate and water. The research conducted by substituting fly ash with sludge. The study used two machines, i.e. GM's existing machine and the machine which constructed by the researcher (Mesin Sendiri=MS). The variation of substituted fly ash ranged from 0.6 kg to 3.60 kg (the last number implies that all fly ash needed in the formula is replaced by sludge). In conclusion, sludge yielded from roof tile production could be used to substitute fly ash in the paving block formulation. Therefore, the substitution method is feasible as roof tile waste utilization technology. During the compressive test, the addition of percentage of substitution material will reduce the strength of paving block. The standard strength of MS paving block is 290 kg/cm2, while the strength of E formula (fly ash is totally replaced with sludge) is 202 kg/cm2. The more percentage of substitution added, the water infiltration increased. Water infiltration value for standard formula and E formula are 3.32% and 6.06% respectively. The water quality analysis shows that the paving block soaking water quality did not excess the recommended value.